Chemical analysis of silica doped hydroxyapatite biomaterials consolidated by a spark plasma sintering method - Xu, Jinling (2012)
Silica (SiO2) and the silicate-based biomaterials play an important role due to their in vitro and in vivo biological response. The present study synthesized a novel nano-structured amorphous silica doped hydroxyapatite (HA) via an aqueous precipitation route. HA was prepared with 0, 1, 3 and 5 wt% silica, which are comparable to the measured silicon content of natural bone. After spray drying into micron sized powders, the silica doped HA (SiHA) powders were consolidated at 1000 C with a dwell time of 3 min using a spark plasma sintering (SPS) technique. X-ray diffraction analysis showed a main apatite phase with minor secondary b-tricalcium phosphate (b-TCP) was observed in the as-consolidated SiHA compacts. Substitution of PO3-